Pengaruh Pemberian Sari Kunyit (Curcuma domestica Val.) dalam Air Minum Terhadap Jumlah Telur Cacing Ascaridia galli pada Ayam Broiler - Herawati Herawati; Djoko Winarso (Jurnal Riset Agribisnis dan Peternakan, 2016)
The purpose of this study was to determine the effect of giving turmeric juice (Curcuma domestic Val.) In drinking water on the number of Ascaridia galli worm eggs in broiler chickens. Chicken feces are collected every week, starting from the second week of 14 days until the fifth week or 35 days of age. The results of this study indicate that the effect of giving turmeric extract (Curcuma domestica Val.) In drinking water on the number of Ascaridia galli worm eggs in broiler chickens can be seen through the fecal collection at the age of 35 days. The data of variance analysis showed that the feces collection was carried out at the age of 14 days, the F count was smaller than the F table 5% (F hit <F tab 5%). The comparison between all treatments given to broilers and controls was not significant. Analysis of variance in fecal collection carried out at 21 days of age until feces collection was carried out at 35 days of age obtained the same results, namely between control (T0) and broiler chickens treated with certain levels of turmeric extract there were very significant differences (P <0.01 ), F table 1% smaller than F count (F tab 1% <F hit). Based on the research, it was concluded that giving turmeric juice in drinking water had a very significant effect on the number of Ascaridia galli worm eggs in broiler chickens. Turmeric juice can reduce the number of Ascaridia galli worm eggs in broiler chickens. Giving turmeric juice at the level of 30 grams / 500 ml (T3) has the same effect as giving turmeric juice at the level of 10 grams / 500 ml (T1). For this reason, giving turmeric juice is recommended at the level of 10 gr / 500 ml because besides being able to save costs, giving at that level has been able to reduce the number of Ascaridia galli worm eggs.